THE AN ANALYSIS OF PLN MOBILE APPLICATION BRANDING EFFORTS IN INCREASING THE NUMBER OF TRANSACTIONS IN MATARAM (A CASE STUDY AT PLN UIW NTB): ANALISIS UPAYA BRANDING APLIKASI PLN MOBILE DALAM MENINGKATKAN JUMLAH TRANSAKSI DI MATARAM (STUDI KASUS PADA PLN UIW NTB) - Feby Yuniasti; Muhammad Jamilludin Nur; Asrin Dimas Tri Fathullah (Program Studi Ilmu Komunikasi Universitas Mataram, 2024)
The users who do transactions on PLN Mobile application are only under 5% in NTB and 12% in Mataram of the total registered Customer IDs, thus PT. PLN UIW NTB needs to make efforts to carry out better branding to increase the number of its transactions. This research aims to find out how PLN UIW NTB's efforts to brand the PLN Mobile application in increasing the number of transactions in Mataram. This research uses a qualitative method with a case study approach. The technique for determining informants used in this research was purposive sampling. The number of informants in this research was 5 people consisting of 1 manager as key informant, 2 assistant managers as main informants, and 2 PLN Mobile application users who had made transactions as supporting informants. The researcher carried out the data collection techniques through interviews, observation, and documentation. This research uses data analysis techniques according to Miles and Huberman with data reduction steps, data presentation, and drawing conclusions. In this research, it was found that PLN UIW NTB carried out branding efforts that could increase the number of transactions on PLN Mobile application by using brand expression theory which consists of brand positioning, brand identity, brand personality, and brand communication. In carried out these efforts, the organization's ability is needed to maintain and increase the company's credibility by upholding the company’s cultural values, which are trustworthy, competent, harmonious, loyal, adaptive, and collaborative.